2014
DOI: 10.1021/jm501241g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure–Activity Relationship Study of Chemical Probes as Hypoxia Induced Factor-1α/Malate Dehydrogenase 2 Inhibitors

Abstract: A structure-activity relationship study of hypoxia inducible factor-1α inhibitor 3-aminobenzoic acid-based chemical probes, which were previously identified to bind to mitochondrial malate dehydrogenase 2, was performed to provide a better understanding of the pharmacological effects of LW6 and its relation to hypoxia inducible factor-1α (HIF-1α) and malate dehydrogenase 2 (MDH2). A variety of multifunctional probes including the benzophenone or the trifluoromethyl diazirine for photoaffinity labeling and clic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…MDH2 enzyme activity was determined by oxaloacetate-dependent NADH oxidation assays as previously described [ 15 ]. The reaction was performed in 100 mM potassium phosphate buffer (pH 7.4) with 0.25 nM rhMDH2, 200 μM oxaloacetic acid, and 200 μM NADH.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MDH2 enzyme activity was determined by oxaloacetate-dependent NADH oxidation assays as previously described [ 15 ]. The reaction was performed in 100 mM potassium phosphate buffer (pH 7.4) with 0.25 nM rhMDH2, 200 μM oxaloacetic acid, and 200 μM NADH.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were incubated for 12 h in the presence or absence of drugs under normoxic or hypoxic condition. After removing the supernatant, luciferase activity was measured using a Dual-Luciferase Assay System (Promega, Madison, WI, USA), according to the manufacturer’s instructions, with a Victor™ X Light luminescence reader [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcineurin B homologous protein 1 (CHP1) was another molecular target protein identified as a target of LW6 in other studies. [23][24][25][26] In another study, we found that heat shock protein (HSP) 70 was a target protein of the phase I clinical candidate adamantyl-based derivative IDF-11774. 27 LW6-based chemical probes were selected from a SAR study of various chemical probes synthesized in our lab.…”
Section: Adamantyl-based Inhibitorsmentioning
confidence: 99%
“…36 For bioluminescence imaging assays, IDF-11774 (50 mg/kg) was administered orally to Balb/c nude mice bearing tumors (100 mm 3 ) formed from HCT116 cells (1 × 10 7 ) expressing HRE-luciferase by subcutaneous injection. After intraperitoneal injection of d -luciferin, bioluminescence images of each tumor were analyzed using the IVIS Lumina II Luminescence Imaging System (Caliper Life Science, Alameda, CA, USA) and Living Image Software (Caliper Life Science).…”
Section: Methodsmentioning
confidence: 99%